Mapping Information Asset Profile In The Implementation Of Risk Management Information System Using Octave Allergo - Haeruddin, . (Universitas Medan Area, 2019)
The development of information systems that are very fast nowadays, encourages every organization to follow in order to escalate the competition. The technology that is widely used today is web-based technology. Apart from being easily accessible and used, this technology is vulnerable to any attacks; so using this information system will bring access risks by those who are not authorized. Therefore, risk management is something that needs to be considered in an organization to minimize the risks that will arise. Mapping the information asset profile can help Universitas Internasional Batam to evaluate, manage risks, and protect assets from the risks that will occur. The researcher used OCTAVE Allergo method in mapping and measuring Information Systems at Universitas Internasional Batam, consists of Academic Information Systems, Academic Portals, Registration Information Systems, Financial Information Systems, HR Information Systems. From the results of this study, Universitas Internasional Batam finds out which impact areas are the most effected: the reputation and customers trust, recognize the information of critical assets, mitigate assets that have high risks, in order to minimize unwanted risks.